Establishment of Vegetation on Exposed Carbonaceous Shale from Cut Slope - Md. Isa, Isharudin (2002)
Shale is a common rock type in Malaysia. Some of the shales are carbonaceous in nature. Carbonaceous shale is exposed during construction of major highways. The instability on cut slopes contributes to soil erosion and in extreme cases slope failure may occur. The susceptibility of cut slopes to landsliding can be reduced in certain circumstances by establishment of a vegetation cover. The objective of this study were to determine the chemical properties of carbonaceous shale, suitable plants mix species and appropriate amendment for carbonaceous shale, and shear strength analysis upon establishment of the vegetation. Initial carbonaceous shale chemical properties were identified before conducting a glasshouse experiment to determine the effect of plant species and soil treatments on dry matter yield in pot experiments consisting of 4 plants specIes, 5 treatments and 4 replications. Completely randomized design was adopted in this experiment. The plants species (Brachiaria ruziziensis, Colopogonium mucunoides, Axonopus affinis and Veteveria zizanioides) were planted and treated with ground magnesium limestone (GML), chemical fertilizer (NPK), organic compost (Com), NPK +GML+compost (NGC) and control (Ctrl). Infiltration rate was determined using modified Double Ring Infiltrometer which was driven into the pot. The plant species that gave a relatively high dry matter yield from the glasshouse experiment Brachiaria ruziziensis and Colopogonium mucunoides were selected for the mix plant species study. The plants were grown in the wooden boxes measuring 20 cm (length) X 20 cm (width) X 100 cm (height). They were treated with compound fertilizer (NPK), NPK + GML (NGL), NPK + GML + foliar fertilizer (Vita-Grow™)(NGF) and control (Ctrl). Complete randomized experimental design was adopted with five replications in this experiment. The shear strength analysis was conducted using the direct shear test method where the angle of internal friction (o) and cohesion (c) were determined from the plotted graph in order to get the shear strength result.